Combating the pandemic of COVID-19 in India: health care worker perspective - Pathak, Barsha Gadapani; Manapurath, Rukman M. (International Journal Of Community Medicine And Public Health, 2020)
As the pandemic of COVID-19 intensifies there is a huge burden on the health care system of each country. As predicted by epidemic model, India with 1.3 billion population and only 0.76 doctors per thousand people will have 1 million people affected by COVID-19 needing ventilatory support. This situation focusses on the substantial thrust on health care workers in India while dealing with the pandemic and protection of the health care workers from COVID-19 infection is significant as they are the key-groups in health system to procure win-battle status against COVID-19. Henceforth, after meticulously comparing various countries’ strategies to protect their HCWs this brief study is being prepared and few recommendations has been suggested which may enable the protection of HCWs in India. Un-interrupted supply of appropriate PPE, phenomenon of presenteeism among HCWs, burn-outs among HCWs, front-line department protocol for protection of HCWs, need of constant psycho-analysis among HCWs, stigma in society for HCWs, prophylaxis for HCWs against COVID-19 and HCWs’ family concerns are some of the issues which are being highlighted in this paper.